Soil–water characterictic curve (SWCC) for FMC Kaolin - Anis Amira, Abdul Karim (2015)
As the world's population has grown and become more urban and affluent, waste production has risen tenfold. Discarded materials are collected, some are recycled or composted, and most are landfilled or incinerated. But in spite of the aggressive economic development, the waste management is relatively poor. This will lead to the contamination of soil at the landfill which raised environmental concern and initiated the involvement of geotechnical engineers in environmental matters. Geoenvironmental engineering covers the aspect of contaminated site remediation and the prevention of future contaminated sites. Clays are one of the alternatives used in the management of wastes disposal at landfills. Clays act as environmental barriers around waste disposal site where they are used as liners and capping materials for landfills sites. Highly plastic clays are used as barriers in landfills and nuclear waste repository. For each application the engineering properties of the clays must be carefully designed to obtain the desired result. Studies concerning changes in the water content as affected by a change in the soil suction are extremely crucial for a long-term assessment of the engineering behaviour of clays. Thus, this thesis experimentally investigated the changes in the water content of initially slurried clay during the drying process. The kaolinite clay which is FMC kaolin was use. The osmotic and vapour equilibrium technique were used in this study to establish soil-water characteristics curve (SWCC) which is subjected to drying process. The graphs of water content over varying suctions and water content over elapsed time are establish for each technique and then combine to show the curve of the drying process ranging from low suction to high suction value. As conclusion, FMC kaolin is suitable to be used as a admixture because of its non-swelling properties where it can absorb water and undergo little volume changes only